Necrotizing Enterocolitis Mortality: A New Parameter to Predict High Risk. Issue 1 (March 2021) - García, Miriam; Casal, Isabel; Pértega, Sonia; González, Cristina; Bouzán, Jesús Caramés
Introduction: Necrotizing enterocolitis, is the most common gastrointestinal emergency in the preterm infant and is associated with high mortality and morbidity. Predict which infants will progress to more severity stages of the illness and are in high risk for mortality is one of the challenges in relation to this disease. The objective of this study is to identify which factors are associated with mortality in infants diagnoses of NEC in our centre along a 12-year period. Material and Methods: A total of 124 consecutively patients were included in the study diagnosed of NEC at the Complejo Hospitalario Universitario de A Coruña, Spain. Information was obtained from medical records to compare patient demographics characteristics, prenatal information, clinical and radiological findings, relevant analytical data, therapeutic management and outcomes of infants who survived NEC and infants who died. Informed consent and ethical review board was obtained. Associations were analyzed by bivariate and multivariate analysis. Results: Among 124 patients, 110 patients survived NEC and 14 died. In multivariate analysis, the patients who died presented at birth low Apgar levels at minute one, apneas in the neonatal period, coagulopathy and low levels of serum proteins at diagnoses of NEC.